Olfactory nerve: from ugly duckling to swan - Mermelstein, Sofia; Pereira, Victor Evangelista Rodrigues; Serrano, Paulo de Lima; Pastor, Rachel Alencar de Castro Araújo; Araujo, Abelardo Queiroz Campos (Arquivos de Neuro-Psiquiatria, 2022)
Background: The olfactory nerve has never been the shining star of neurological examination. Quite the contrary, examining the first cranial nerve is often an overlooked step. As cases of anosmia secondary to COVID-19 infection continue to rise, the 2020 pandemic has shed new light on this much-forgotten nerve, its value as an aid to diagnosis of several diseases and its central role in our daily lives. Objective: We aimed to emphasize how essential and simple clinical examination of the olfactory system can be by highlighting practical techniques and clinical tips for its assessment. We also share pearls and pitfalls in localization and differential diagnosis, which may prove valuable to busy clinicians. Methods: A broad review of the literature was conducted by searching PubMed, Cochrane and Google Scholar for articles and books containing topics regarding examination of the olfactory nerve and its anatomy, physiology and pathology. No particular inclusion or exclusion criteria were used. Results: Forty different works were found, between books and articles, from which 20 were selected after careful analysis. Conclusions: Despite the tragedy and adversity that followed the COVID-19 pandemic, its legacy has taught us a crystal-clear lesson: olfaction should no longer be neglected in clinical practice.
Keywords: Clinical Neurology; Smell; Infectious Disease; Olfactory Nerve